PENGARUH MINDFULNESS MEDITATION: SELF-COMPASSION TERHADAP FEAR OF CHILDBIRTH PADA IBU HAMIL TRIMESTER III DI PUSKESMAS KECAMATAN PASAR REBO - Aisyah Nur Fadhillah (2023)
Fear of childbirth (FOC) is pregnancy-related anxiety felt by mothers during pregnancy until before delivery. FOC is triggered by the mother's bad thoughts about what might happen to herself and the fetus such as bleeding, tearing of the birth canal and other complications to the delivery procedure. Globally, FOC has increased since 2015 by 16%. This figure is much lower than the incidence rate reported by several studies from various parts of the world, in Egypt, which found FOC rates of 51.3% primigravida and 61.2% multigravida. In Indonesia, the incidence of FOC is still relatively high, amounting to 45.2% of primigravida experiencing a very high FOC category. FOC can be overcome with self-compassion which is one type of mindfulness meditation. This study aims to determine the effect of mindfulness meditation: self-compassion on fear of childbirth in pregnant women in the third trimester. This study was conducted by pre-experimental method with one group pretest-posttest design with a total of 35 respondents. The sampling technique used is accidental sampling. The results showed that mindfulness meditation: self-compassion had a significant effect on reducing the level of fear of childbirth in pregnant women in the third trimester with a p-value of 0.000 (p>0.05).